Orthographic and Morphological Masked Priming Effects in Arabic: Evidence from Lexical Decision Task in Children with and Without Dyslexia. Issue 3 (3rd April 2019) - Layes, Smail; Khenfour, Hichem; Lalonde, Robert; Rebai, Mohamed
Abstract : In this study, we conducted a lexical decision test using masked priming paradigm to examine the morphological and orthographic priming effects in word recognition. Morphologically related word pairs can be derivational, sharing the same root or not (pseudo derivational). However, the orthographically related pairs share the same letters in different positions. Two groups of native Arabic-speaking children ( N = 57) from grade 4 and 5 participated in this study: typical readers ( n = 39) and dyslexic readers ( n = 18). To examine whether a potential morphological priming effect is driven by semantic or orthographic properties of shared morphemes, we compared prime-target pairs with derivation morphology and pseudo-derivation word related pairs. Between groups comparisons showed that a priming effect occurred only in typical readers. Comparisons between conditions revealed that a priming effect only occurred for accuracy in derivational morphology. No priming effect occurred in reaction times (RTs) between groups or conditions. These results provide evidence for root-based word recognition in Arabic children and give support to semantically rather than orthographically driven lexical access.